2014
DOI: 10.1002/jctb.4451
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of biodegradable foam from walnut shells treated by subcritical water

Abstract: BACKGROUND: Subcritical water treatment is considered an environment-friendly method to liquefy biomass to prepare valuable chemicals. Several researchers have studied the solid obtained after autohydrolysis treatment for use as reinforcement in biocomposities and was the base pulp and paper technologies. The novelty of this present research is the use of solid in the manufacture of starch foams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A great amount of walnut shell is available after fruit processing in walnut kernel production centers, yet only a limited amount has been used in industry. 59 In fact, most of it is discarded as waste material or used as fuel for burning applications. 44 But this causes pollution of the environment, and it also has a low utility value.…”
Section: Walnut Shellmentioning
confidence: 99%
See 1 more Smart Citation
“…A great amount of walnut shell is available after fruit processing in walnut kernel production centers, yet only a limited amount has been used in industry. 59 In fact, most of it is discarded as waste material or used as fuel for burning applications. 44 But this causes pollution of the environment, and it also has a low utility value.…”
Section: Walnut Shellmentioning
confidence: 99%
“…Various methods have been suggested for the hydrolysis of cellulose and hemicellulose in wood biomass as a means of producing carbohydrates, which are good sources for the production of bioethanol. 59 Another effective method for the utilization of walnut shells is the production of charcoal and activated carbon by executing pyrolysis. 67 During the production of charcoal, the generated gases are usually discharged into the air.…”
Section: Walnut Shellmentioning
confidence: 99%
“…Fruit growth and development are a major research interest (Pinney and Polito, 1983;Wu et al, 2009) as well as the composition and nutritional value of the seed (Fukuda et al, 2003;Kornsteiner et al, 2006;Zhang et al, 2009;Martinez et al, 2010). In recent years, the walnut shell has also been studied due to its potential for the production of bioethanol (Yang et al, 2015;Lancefield et al, 2017), pyroligneous acid (Jahanban-Esfahlan and Amarowicz, 2018), charcoal and activated carbon (Xie et al, 2013) and "nutty carbon, " which is used for Na-ion battery anodes (Wahid et al, 2017). For novel applications and material development, fundamental knowledge of the structure as well as the chemistry of the shell is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The residue after hydrolysis is rich in cellulose and lignin, which can be further utilised. Yang et al [5] reported that the optimal conditions for the recovery of carbohydrates (about 400 mg TCH/g walnut shells) from walnut shells with subcritical water are 200 • C and 15 min. The residue from the walnut shells was used to produce a biodegradable foam by mixing it with corn starch.…”
Section: Total Carbohydrates Contentmentioning
confidence: 99%
“…The total global production of pistachios and walnuts (in-shell) in 2022/2023 is estimated to be 747.31 thousand tons [2] and 2.6 million tons [3], respectively. The shell of walnuts consists of 22.2-30.2% hemicellulose, 25.5-27.9% cellulose and 39.1-52.3% lignin [4,5], while the shell of pistachios consists of 20-32% hemicellulose, 30-55% cellulose and 12-38% lignin [6,7]. Usually agricultural biomass waste (walnut and pistachio shells) is incinerated to generate heat.…”
Section: Introductionmentioning
confidence: 99%